Sustainable Tax Recovery to Prevent Tax Fraud in The Jabodetabek Area - Andaningsih, IGP Ratih; Novita, Novita; Nugrahanti, Trinandari Prasetya; Arif, Elsya Meida (International Journal of Pertapsi, 2024)
In Conducting this field research,researchers conducted field research related to the practice of implementing tax and anti fraud (Tax Fraud) among MSMEs business players in Indonesia which refers to Law No 7 of 2021 in relation to economic recovery in the field of tax reform.The Aim to be achieved in this research to increase revenue .The research method used are used combinations a qualitative method and a quantitative method. A qualitative method used a symetric method with action research, critical analysis, quantitative narrative analysis, a Interviews and practical interview models and field observations with a symetric partial interest analysis approach using informant data. Representatives of business actors in the Jabodetabek area and surroundings areas, in Indonesia which has a gross turnover of 100 million per month. This research is very useful for increasing the potential and revenue of regional taxes and central taxes in the MSMe business distribution sector optimally and optimally. The contribution of the research is to increase tax revenues, especially the MSMe taxation sector. The results of the research are to increase the culture of awareness of paying taxes and be able to increase sources of state revenue.